The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.21070/mid.v1i2.349
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan Ibu Tentang Penanggulangan Diare Dengan Penatalaksanaan Diare Balita Usia 1-5 Tahun

Abstract: Mother's knowledge about prevention of diarrhea can cause diarrhea deteriorate that leads to death or getting better, depend on the management of diarrhea that mother do. The purpose of the present study is to find out the relationship between mother's knowledge on diarrhea prevention against treatment of diarrhea in children 1-5 years. This research method is a survey research with cross sectional approach and point-time models.The population of the study is all mothers who have children 1-5 years old in Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…67.35% children were not affected by diarrhea. This study is also not in line with the results of research in Jemowo village which showed that there was a relationship between maternal knowledge about diarrhea control against diarrhea management in children aged 1-5 (p-value 0.000) [11].…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…67.35% children were not affected by diarrhea. This study is also not in line with the results of research in Jemowo village which showed that there was a relationship between maternal knowledge about diarrhea control against diarrhea management in children aged 1-5 (p-value 0.000) [11].…”
Section: Resultscontrasting
confidence: 95%
“…Also. low knowledge of breast milk and colostrum causes the mother to often discard breast milk and colostrum because they are considered not useful [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation